The Last Universal Common Ancestor of Ribosome-Encoding Organisms: Portrait of LUCA - Forterre, Patrick (Journal of molecular evolution, 2024)
The existence of LUCA in the distant past is the logical consequence of the binary mechanism of cell division. The biosphere in which LUCA and contemporaries were living was the product of a long cellular evolution from the origin of life to the second age of the RNA world. A parsimonious scenario suggests that the molecular fabric of LUCA was much simpler than those of modern organisms, explaining why the evolutionary tempo was faster at the time of LUCA than it was during the diversification of the three domains. Although LUCA was possibly equipped with a RNA genome and most likely lacked an ATP synthase, it was already able to perform basic metabolic functions and to produce efficient proteins. However, the proteome of LUCA and its inferred metabolism remains to be correctly explored by in-depth phylogenomic analyses and updated datasets. LUCA was probably a mesophile or a moderate thermophile since phylogenetic analyses indicate that it lacked reverse gyrase, an enzyme systematically present in all hyperthermophiles. The debate about the position of Eukarya in the tree of life, either sister group to Archaea or descendants of Archaea, has important implications to draw the portrait of LUCA. In the second alternative, one can a priori exclude the presence of specific eukaryotic features in LUCA. In contrast, if Archaea and Eukarya are sister group, some eukaryotic features, such as the spliceosome, might have been present in LUCA and later lost in Archaea and Bacteria. The nature of the LUCA virome is another matter of debate. I suggest here that DNA viruses only originated during the diversification of the three domains from an RNA-based LUCA to explain the odd distribution pattern of DNA viruses in the tree of life.